2020
DOI: 10.1364/oe.382485
|View full text |Cite
|
Sign up to set email alerts
|

Tunable electromagnetically induced transparency based on graphene metamaterials

Abstract: In this paper we propose a graphene-based metasurface structure that can exhibit tunable electromagnetically-induced-transparency-like (EIT) spectral response at mid-infrared frequencies. The metasurface structure is composed of two subwavelength mono-layer graphene nano-disks coupled with a mono-layer graphene nano-strip. We show that the coupling of the nano-disks’ dipole resonance with the quadrupole resonance of the nano-strip can create two split resonances with a transparency window in between at any des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Currently, the EIT-like effect in terahertz (THz) MSs has been widely investigated and experimentally demonstrated by bright–dark mode coupling [ 6 , 7 ] or bright–bright mode coupling [ 8 , 9 ]. Unfortunately, most of these structures can only realize a single transparency window, in which the resonance strength of the window is fixed after fabrication, restricting their application fields [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the EIT-like effect in terahertz (THz) MSs has been widely investigated and experimentally demonstrated by bright–dark mode coupling [ 6 , 7 ] or bright–bright mode coupling [ 8 , 9 ]. Unfortunately, most of these structures can only realize a single transparency window, in which the resonance strength of the window is fixed after fabrication, restricting their application fields [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, achieving tunability of results has become a major research focus. [17][18][19][20] There are many types of active or tunable materials in nature that have been incorporated into metamaterials, such as ferroelectrics, 21 liquid crystals, 22,23 semiconductors, 24,25 two-dimensional materials, [26][27][28][29] and phase change materials. 30,31 Xiao et al proposed a graphene-based metasurface structure that exhibits a tunable EIT response under mid-infrared frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrated that EIT responses can be dynamically shifted in the frequency domain by adjusting the Fermi level of graphene. 26 Xiao et al investigated a planar terahertz EIT metamaterial to realize the maximum modulation depths in two perpendicular polarization directions (83.54% and 94.39%, respectively) by tuning Fermi energy. 32 Xu split rings.…”
Section: Introductionmentioning
confidence: 99%
“…The rings of each group have the same scale and are symmetrical about the Y axis. The ion-gel and conductive layer, described by a nondispersive permittivity ε=1.82 [44], are attached to the top of the entire structure. The voltage is tuned by the Au gate fabricated on the ion-gel layer, thereby tuning the Fermi energy level of the graphene metasurface.…”
Section: Introductionmentioning
confidence: 99%